An experimental investigation on sunlight absorption characteristics of silver nanofluids. (May 2015) - Chen, Meijie; He, Yurong; Zhu, Jiaqi; Shuai, Yong; Jiang, Baocheng; Huang, Yimin
Highlights: Silver nanoparticles were added to improve the photo-thermal conversion efficiency. Silver nanofluids perform much better at very low concentrations. Efficiency of silver nanofluid is twice of water at first with concentration of 80.94 ppm. The highest SAR has reached 827 W/g at the lowest concentration of 20.24 ppm. Abstract: In this work, plasmonic silver nanoparticles were added to a working fluid to improve its solar thermal conversion efficiency. Silver nanoparticles were synthesized by a novel photochemical transformation of aqueous silver nanoparticle precursors, which was reduced by NaBH4 using Polyvinyl Pyrrolidone (PVP) and sodium citrate stabilizers. Experimental results showed that silver nanofluids performed much better at very low concentrations than other working fluids at relatively high concentrations exposed to both simulated and natural sunlight. Under simulated sunlight, the efficiency of the silver nanofluid is 84.61% after 5 min irradiation with a mass concentration of 80.94 ppm, which was almost twice that of water and also much higher than that of ZnO nanofluid (mass concentration of 1.02%) and TiO2 nanofluid (concentration of 0.7%). The efficiency of the low concentration Ag nanofluid improved with the increase of nanoparticle concentration. With the increase of irradiation time, both the temperature increment and Specific Absorption Rate ( SAR ) decreased, which showed that the effect of nanofluid as a working fluid in a solar collector was great at the beginning, this is to say at the lower end of the temperature range. After 5 min, at the lowest concentration of 20.24 ppm, the highest value of SAR reached ∼827 W/g.